2005
DOI: 10.1111/j.1471-4159.2005.03057.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide Y stimulates neuronal precursor proliferation in the post‐natal and adult dentate gyrus

Abstract: Adult dentate neurogenesis is important for certain types of hippocampal-dependent learning and also appears to be important for the maintenance of normal mood and the behavioural effects of antidepressants. Neuropeptide Y (NPY), a peptide neurotransmitter released by interneurons in the dentate gyrus, has important effects on mood, anxiety-related behaviour and learning and memory. We report that adult NPY Y -/-1 receptor knock-out mice have significantly reduced cell proliferation and significantly fewer imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
178
2
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 169 publications
(208 citation statements)
references
References 73 publications
27
178
2
1
Order By: Relevance
“…Interestingly, the basal level of proliferation was not affected by U0126 microinfusion, indicating that the MAPK pathway is not required for constitutive cell division. This observation is similar to a recent report by Howell et al (2005) showing that neuropeptide Y (NPY)-mediated MAPK pathway activity blocked inducible but not the basal level of proliferation. With respect to inducible proliferation, our data are consistent with a number of recent studies implicating MAPK signaling in progenitor cell proliferation.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, the basal level of proliferation was not affected by U0126 microinfusion, indicating that the MAPK pathway is not required for constitutive cell division. This observation is similar to a recent report by Howell et al (2005) showing that neuropeptide Y (NPY)-mediated MAPK pathway activity blocked inducible but not the basal level of proliferation. With respect to inducible proliferation, our data are consistent with a number of recent studies implicating MAPK signaling in progenitor cell proliferation.…”
Section: Discussionsupporting
confidence: 91%
“…3A). Furthermore, when examining NPY-induced ERK signaling pathway as reported previously [14,16,19,34], NPY failed to activate activity-related site-specific phosphorylation of ERK (Thr202/Tyr204) in isolated adipocytes while NE stimulated it (Fig. 3B).…”
Section: Resultssupporting
confidence: 77%
“…NPY has been shown to activate ERK pathway in a variety of cells, possibly leading to cell proliferation of neuronal precursor cells [14,16] and progression of cancer [34]. Moreover, Yang et al…”
Section: Discussionmentioning
confidence: 99%
“…Investigation of olfactory neuronal precursor cells in mice with a targeted deletion of NPY revealed a reduction in neuronal precursor proliferation resulting in fewer olfactory neurons (42) and indicated that NPY is required for the normal proliferation of olfactory neurospheres in vitro. (43) Similarly, NPY has been shown in mice to promote the proliferation of neuronal progenitor cells in the dentate gyrus of the hippocampus (28,44) and also in the subventricular zone. (45,46) Interestingly, in all cases, the Y receptor mediating these effects is the Y1 receptor.…”
Section: Discussionmentioning
confidence: 99%